Respuesta :

Answer:

drag each result in the corresponding box according to the results

Step-by-step explanation:

Hello

The product of two or more powers of equal  base "a" is equal to the power of base  "a" with   exponent equal to the sum of the respective exponents.

[tex]a^{m}*a^{n} =a^{n+m}[/tex]

Step 1

[tex]d*2d^{2}\\[/tex]

[tex]d*2d^{2}=(2*1)d^{(2+1)}\\d*2d^{2}=2d^{3} \\[/tex]

Step 2

[tex]-9*2d^{2}\\[/tex]

[tex]-9*2d^{2}=(-9*2)d^{(2+0)}\\-9*2d^{2}=-18d^{2} \\[/tex]

Step 3

[tex]d*11d\\[/tex]

[tex]d*11d=(1*11)d^{(1+1)}\\11*d^{2}=11d^{2} \\[/tex]

Step 4

[tex]-9 * 11d\\[/tex]

[tex]-9 * 11d = (-9*11)d^{1+0}=-99 d[/tex]

Step 5

[tex]d*-4=-4d[/tex]

Step 6

[tex]-9*-4 = ( -*- ) (9*4)= 36[/tex]

Step 7

Now, drag each result in the corresponding box .

Have a great day

Answer:

Your welcome :)

Step-by-step explanation:

Ver imagen cherrycakejam101
ACCESS MORE